Accelerating Methane Reductions in Rice Production in Southeast Asia - International Rice Research Institute (International Rice Research Institute, 2025)
This report summarizes the discussions during the regional stakeholder dialogue and project launch workshop organized by the International Rice Research Institute on Accelerating Methane Reductions in Rice Production in Southeast Asia—Regional Launching and Consultation Workshop, held on 11 to 13 March 2025 in Manila, Philippines. This regional stakeholder consultation was carried out jointly by the newly launched project on Accelerating scaling of LowEmissions Rice in Southeast Asia (AcceLER), funded by Global Methane Hub (A-2024-18); Accelerating methane reductions in rice production systems through market-based mechanisms (AMR), funded by Clean Climate and Air Coalition (A-2022-110), and the Methane Accelerator in Southeast Asia project (MASEA) (A-2023-108).